PENGARUH KEPEMIMPINAN, PROGRAM SERTIFIKASI, DAN PENGEMBANGAN KEPROFESIONALAN TERHADAP KINERJA GURU PADA SMA NEGERI DI KABUPATEN BANYUWANGI - KARIMAH, AKHLAKUL (Journal of Accounting and Business Education, 2014)
Education is a place that aims to establish and educate a qualified Human Resources, have expertise and can build the character of the nation that is able to compete in the field of science and technology that fear of God Almighty and virtuous noble character. This study aims to determine the effect of leadership, certification programs and professional development on teacher performance in high schools in Banyuwangi.The population is the number of teachers 531 Civil ServantsÂ  that has been certified in 17 state high schools throughout Banyuwangi. Sampling in this study using the proportional random sampling with 105 teachers. The model used in this study is a model of causality or influence relationships. To test the hypothesis that will be proposed in this study the analysis techniques to be used is SEM or Structural Equation Modeling program operated through AMOS.The study shows that leadership and certification programs affect to improve the performance of teachers through professional development. Where leadership affect professional development of teachers with a coefficient of 0.43. The certification program is a variable that affects the professional development of teachers with a coefficient of 0.48. Impact of school leadership on teacher performance with a coefficient of 0.23. The certification program has an influence on performance improvement of teachers with a coefficient of 0.22. Professional development that affects the performance of teachers with a coefficient of 0.12. And leadership and certification programs to improve the performance of teachers through professional development with a coefficient of 0.33.